Analysis of Pedagogical Content Knowledge (PCK) Capabilities of Preservice Elementary School Teachers through Science Learning Planning - Yanti, Meili; S, Muhammad Ilham; Astiti, Niken Yuni (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Ilmu Keguruan IAIN Manado, 2024)
Science material is often abstract, making it difficult for elementary school students to understand. Therefore, teachers need special abilities in designing their learning. So this is a problem for most elementary school teachers. The ability to design science learning in this research is referred to as Pedagogical Content Knowledge (PCK). PCK helps teachers combine in-depth knowledge of subject matter with effective teaching strategies. This allows teachers to deliver material in a way that suits the cognitive development and learning needs of elementary school students. Therefore, this research aims to provide an overview of the PCK abilities of prospective elementary school teachers in designing science lessons. This research is descriptive research which is in line with the research objective, namely to provide an overview of the PCK abilities of prospective elementary school teachers in designing science learning. Participants in this research were 14 students in the fourth semester of the Primary School Teacher Education Study Program (PGSD), Faculty of Teacher Training and Education (FKIP), West Sulawesi University. Data was obtained through a learning design assessment sheet that was oriented towards PCK abilities. Data collection is carried out by asking students to create a learning plan, then the design is assessed using an assessment sheet. The PCK abilities of prospective elementary school teachers are considered varied, where the ability to choose methods is quite good but in terms of mastery and development of teaching materials is still lacking. This is due to the lack of experience of prospective teachers in teaching and the acquisition of science content material only obtained in one course. The implications of this research can be used as a reference for educational curriculum development, especially in elementary school teacher education study programs.